The key target of neuroprotection after the onset of ischemic stroke: secretory pathway Ca(2+)-ATPase 1 - Li, Li-hua (Neural Regen Res, 2015)
The regulatory mechanisms of cytoplasmic Ca(2+) after myocardial infarction-induced Ca(2+) overload involve secretory pathway Ca(2+)-ATPase 1 and the Golgi apparatus and are well understood. However, the effect of Golgi apparatus on Ca(2+) overload after cerebral ischemia and reperfusion remains unclear. Four-vessel occlusion rats were used as animal models of cerebral ischemia. The expression of secretory pathway Ca(2+)-ATPase 1 in the cortex and hippocampus was detected by immunoblotting, and Ca(2+) concentrations in the cytoplasm and Golgi vesicles were determined. Results showed an overload of cytoplasmic Ca(2+) during ischemia and reperfusion that reached a peak after reperfusion. Levels of Golgi Ca(2+) showed an opposite effect. The expression of Golgi-specific secretory pathway Ca(2+)-ATPase 1 in the cortex and hippocampus decreased before ischemia and reperfusion, and increased after reperfusion for 6 hours. This variation was similar to the alteration of calcium in separated Golgi vesicles. These results indicate that the Golgi apparatus participates in the formation and alleviation of calcium overload, and that secretory pathway Ca(2+)-ATPase 1 tightly responds to ischemia and reperfusion in nerve cells. Thus, we concluded that secretory pathway Ca(2+)-ATPase 1 plays an essential role in cytosolic calcium regulation and its expression can be used as a marker of Golgi stress, responding to cerebral ischemia and reperfusion. The secretory pathway Ca(2+)-ATPase 1 can be an important neuroprotective target of ischemic stroke.